The Anatomy of Coolness - Corbanese, Eleonora (ZoneModa Journal, 2020)
In this paper I will describe how I designed and which are my findings of the research I undertook for my dissertation project during my Master in Fashion at Goldsmiths, University of London in late 2017. I dealt with the meaning of coolness, unpicking its definition and problematizing its role in contemporary culture. The aim of the whole research project was to shape my own definition of coolness, within the realm of everyday life, using it as a tool to explore my interests; at the same time, it triggered enticing conversations with people about their personal response to fashion-led practices. In order to decode coolness, I crossed my theory-based framed research with research on the field. The former is mainly based on sociologist Joanne Entwistle’s take on the theory of the “social body,” explained in her book The Fashioned Body; sociologist Joanne Finkelstein’s adaptation of Baldassarre Castiglione’s term sprezzatura to nowadays popular culture in her book The art of self-invention; and journalist Dick Pountain and sociologist David Robins’ book Cool Rules: Anatomy of an attitude. The latter is constituted by a visual survey, in which I asked people to draw a response to the question ‘What is cool for you?’; observation on the streets taking pictures that I then elaborated and transformed in an illustrated handbook entitled The Anatomy of Coolness and a workshop, that I organized at Goldsmiths, focused on the female body, entitled I didn’t want the body missing. Firstly, I will give a theoretical framework of the project, and I will analyse the agency and meaning of coolness in relation to the wider and more established definition of style. In the second part of this paper I will address more directly on three activity of the research path I designed. I will explain my methodology and the analysis of the findings I gathered through my field research.